2020
DOI: 10.3892/mmr.2020.11542
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA TPTEP1 inhibits stemness and radioresistance of glioma through miR‑106a‑5p‑mediated P38 MAPK signaling

Abstract: Glioma is diagnosed as the most common intracranial malignant tumor. cancer stem cells determine stemness and radioresistance, and may facilitate glioma recurrence. The present study aimed to investigate whether the long non-coding rna (lncrna) transmembrane phosphatase with tensin homology pseudogene 1 (TPTeP1) regulated cell stemness and radioresistance of glioma, and determine the underlying molecular mechanism of TPTeP1 in the modulation of glioma progression. cell and molecular biology techniques were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“… 21 Another study identified that indeed miR‐106a‐5p was highly expressed and associated with a poor prognosis in triple‐negative breast cancer. 22 Studies on gastric cancer 23 and hepatocellular carcinoma 24 also confirmed that miR‐106a‐5p indeed played a vital role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“… 21 Another study identified that indeed miR‐106a‐5p was highly expressed and associated with a poor prognosis in triple‐negative breast cancer. 22 Studies on gastric cancer 23 and hepatocellular carcinoma 24 also confirmed that miR‐106a‐5p indeed played a vital role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 90%
“… 17 Many studies have shown that the main function of miR is to control tumour progression, and one such miR is miR‐106a‐5p. 21 , 22 A study on ovarian cancer identified miR‐106a‐5p could promote tumour progression by binding and regulating the target gene ARHGAP24. 21 Another study identified that indeed miR‐106a‐5p was highly expressed and associated with a poor prognosis in triple‐negative breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the p38 MAPK pathway has been also involved in cervical cancer through the miR-409-3p/CDK8 axis [ 49 ]. In glial tumors, a modulation of the p38 MAPK signaling pathway through miR-106a-5p suppressed glioma stemness and radioresistance [ 50 ] In pancreatic cancer, miR-27a-3p was involved in the induction of apoptosis via the modulation of p38 MAPK through the upregulation of the long noncoding RNA DGR5 [ 51 ].…”
Section: The P38 Mapk Pathwaymentioning
confidence: 99%
“…The transmembrane phosphatase with tensin homology pseudogene 1 (TPTEP1) lncRNA is one of the most downregulated lncRNAs in non-small cell lung cancer, where it inhibits the cell proliferation by competitively sponging miR-328-5p [ 58 ]. In glioma, TPTEP1 promotes the P38 MAPK pathway through competitive interactions with miR-106a-5p, thus inhibiting stemness and radioresistance [ 59 ].…”
Section: Lncrnas In Signaling Pathways and Brain Tumorsmentioning
confidence: 99%